Identification of glucose and insulin patterns during A 5-H glucose tolerance test and association with cardiometabolic risk factors - Paulina B. Crespo-Morfin; Carlos A. Aguilar-Salinas; Paloma Almeda-Valdés; Raúl Alfaro-Pastrana; Omar Y. Bello-Chavolla; Jhoana Cano-Castillo; Francisco J. Gómez-Pérez; Ivette Cruz-Bautista (Permanyer, 2022)
Background: Insulin resistance is key in the pathogenesis of the metabolic syndrome and cardiovascular disease. Objective: We aimed to identify glucose and insulin patterns after a 5-h oral glucose tolerance test (OGTT) in individuals without diabetes and to explore cardiometabolic risk factors, beta-cell function, and insulin sensitivity in each pattern. Methods: We analyzed the 5-h OGTT in a tertiary healthcare center. We identified classes using latent class trajectory analysis and evaluated their association with cardiometabolic risk factors, beta-cell function, and insulin sensitivity surrogates by multinomial logistic regression analysis. Results: We included 1088 5-h OGTT performed between 2013 and 2020 and identified four classes. Class one was associated with normal insulin sensitivity and secretion. Class two showed hyperglycemia, dysinsulinism, and a high-risk cardiometabolic profile (obesity, hypertriglyceridemia, and low high-density lipoprotein [HDL] cholesterol). Class three included older individuals, a higher proportion of males, and a greater prevalence of hypertension, hyperglycemia, hyperinsulinemia, and postprandial hypoglycemia. Finally, class four showed hyperglycemia, dysinsulinism, and hyperinsulinemia; this class had the worst cardiometabolic profile (a high proportion of males, greater age, hypertension, obesity, hypertriglyceridemia, and low HDL cholesterol, p < 0.001 vs. other classes). Conclusions: The latent class analysis approach allows the identification of groups with an adverse cardiometabolic risk factor, and who might benefit from frequent follow-ups and timely multidisciplinary interventions.